(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Contusion of the globe is an injury resulting from a blunt object. Despite advances in imaging techniques, the detection of the pathology in contusion of the eye is still a challenge for the ophthalmologist. Purpose: To assess visualization of anterior eye structures by near-infrared transpalpebral transillumination (NIR TPT) in patients with contusions of the globe. Material and Methods: Twenty-five patients with a moderate or severe uniocular contusion who presented 2 to 15 days after the traumatic event were under observation. The fellow eye was intact in all cases. Patients underwent visual acuity assessment; biomicroscopy; ophthalmoscopy; intraocular pressure (IOP) measurements; ultrasound scanning of the anterior eye and posterior eye; ultrasound distant perimetry; X-ray examination; color photography and NIR TPT. Results: NIR TPT enabled identifying various types of damage to the iris, lens and sclera, including subconjunctival scleral ruptures. Pars plicata width was larger in affected eyes than in intact fellow eyes. Conclusion: NIR TPT enables non-invasive visualization of various types of damage to the anterior eye like iridodialysis in the iris root area, tears of the pupillary margin, lenticular opacity, subluxated lens and subconjunctival scleral ruptures in patients with contusion of the globe. In addition, for these study patients, pars plicata width was larger in affected eyes than in intact fellow eyes.